Comportamento de caracteristicas e propriedades fisicas de um podzolico vermelho-amarelo sob condicoes de pasto natural e cultivo na regiao de Lavras, Minas Gerais - Oliveira, Maurício de (1979)
Soil physical characteristics and soil physical prooerties of an Ultisol (Red-Yellom Podzolic) from the region of Lavras, State of Minas Gerais, Brazil, more evaluated under laboratory conditions in order to compare three profiles, respectively under natural pasture and cultivation for 10 consecutive years. The characteristics and properties studied tuere: 1. particle size analysis and textural ratio 2. total, u/ater dispersed clay and flocullation mdex 3. soil aggregation 4. organic matter and free Fe₂0₃ 5. particle density 6. bulk denôity 7. total, macro and microporosity 8. Atterberg's limits. Other Chemical characterization included cation exchange complex in both soil profiles. Correlations for physical characteristics and properties and other chemical properties of the soil profiles uiere established to compare data for cultivated and natural pasture área. Cultiuation led to considerable changes in some of the soil physical characteristics and soil physical properties studied that are importante to plant development and erosion resistance.Soil cultivation cultivation increased the values for bulk density and microporosity, snowing also anigher levei for soil compaction in A₁ and A 4 B horizons, and, consequently increasing erosion hazards due to reduction in macroporosity and in infiltration/run-off ratio. Cultivated soil is more subjected to losts of the yield potencial, being necessarv soil conservation practices to reduce deleterius effects of soil cultivation and increase soil productivity. Chemical and physical analysis suggested that cultivated area presented more advanced degree of weathering compared to natural pasture condition in B₃₁(Bsq-1), B₃₂(Bsq-2) and B₃₃(Bsq-3) horizons for cultivated soil profiles at 131-165 cm, 165-200 cm, and 166-200 cm depth, respectively.